Recent advances in cobalt based heterogeneous catalysts for oxygen evolution reaction - Afreenuzzaman Badruzzaman (17115631) (2020)
The future of the world energy lies in clean and renewable energy sources. Many technologies, such as solar cells, wind turbines, etc., have been developed to harness renewable energies in different forms of fuel. Amongst them, electrolysis of water to produce oxygen and hydrogen is one of the paramount developments towards achieving clean energy, which has attained significant attention due to its green and simple method for the production of fuels. In electrolysis of water, the half-reaction containing the oxygen evolution reaction (OER) is a reaction that is kinetically sluggish, which requires higher overpotential to produce O2, when compared to the other half-reaction, i.e. hydrogen evolution reaction (HER). Many electrocatalysts are studied extensively to be used in the OER process to get an economical yield out of it. Noble metal-based catalysts are the state-of-the-art catalyst used for OER currently. But due to their high cost and scarcity, they cannot be applied in a large-scale manner to be used in the future. The non-noble metals (transition metals and perovskites) are gaining interest by exhibiting on par or better OER performance compared to the noble metal used. Due to their low cost, ample resources, and several metals available, they have opened up a variety of areas with a different combination of metals to be used as a catalyst for OER. Amongst these metals, cobalt has received massive appreciation for performing as an excellent OER catalyst. Multi metals, multimetal mixed oxides, multimetal phosphides, perovskites, and carbon-supported catalysts containing cobalt have shown low overpotential with high long-term stability. Therefore, in this review, we go through different cobalt-based electrocatalysts for OER, the general mechanism governing the OER process, the challenges that we are facing today to enhance the catalytic performance, and future aspects to overcome such challenges. Other Information Published in: Inorganica Chimica Acta License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ica.2020.119854